An investigation of how members of a school governing body perceive and experience their roles : a case study - Lusaseni, Pamella Hombakazi (Rhodes University, Faculty of Education, Department of Education, 1999)
Education in South Africa is currently facing a lot of changes. This study was prompted by one of these changes, the introduction of a School Governing Body (SGB), constituted in terms of the 1996 Schools Act (South Africa 1996), and replacing the previous Parent-Teacher-StudentAssociation (PTSA). The study investigates how the members of a School Governing Body perceive and experience their roles, in an attempt to make a contribution to understanding the nature and implications of education governance policy in South Africa. Central to this exercise is the attempt to understand how the execution of their duties, their practice of both democracy and accountability, and their resolving of tensions and/or differences among parents, teachers and students, impacts upon their school generally and relates both to the Department of Education and other organs of society. The methodology employed in this study includes a review of relevant literature, international and national, followed by a historical overview of education governance in South Africa. The core of the thesis is an interpretive case study of the SGB of one junior secondary school under the auspices of the Department of Education, Culture and Sport, in the South Eastern region of the Eastern Cape Province. The single most important data gathering instrument used was a series of in-depth interviews. The interviewees were the Executive members of the SGB of the school. The major findings of the study were that the SGB was powerful and effective in its area of operation in school governance, despite its lack of skills in the execution of its duties. Many of the difficulties it has encountered can be ascribed to a lack of guidance from the Department of Education. The study thus concludes that whereas the SGB studied represents an important step towards the full democratization of education in general and in this school in particular, its role in school governance can not be described as an unqualified success. However, despite the problems faced by the SGB, its role has made history in the governance of the school. Programmes which the SGB has implemented, such as measures to foster a culture of teaching and learning, have had an important impact on the progress of the school. Finally, the findings of the study indicate that the most important issues to be addressed in respect of the SGB researched are capacity building, communication, cultural understanding and the level of SGB understanding of the Schools Act. The study makes certain recommendations for the attention of SGBs and the Department of Education. These include a well co-ordinated capacity building prograrn to be developed and implemented, that will provide SGBs with access to knowledge of the relevant material and other resources necessary to sustain school governance functions. Because of the limited nature of the study in terms of methodology and constraints of time, the conclusions arrived at cannot and should not be generalized beyond the confines of the study.
Keywords: School management and organization -- South Africa; School boards -- South Africa; Educational leadership; School personnel management